GAMBARAN PENGGUNAAN BAHAN TUMPATAN DI POLIKLINIK GIGI PUSKESMAS KOTA BITUNG TAHUN 2014 - Lengkey, Catra H. E.; Mariati, Ni Wayan; Pangemanan, Damajanty H. C. (e-GiGi, 2015)
Abstract: Health is an important thing for every human being and caries is a health problem that damaging email and dentin structure of teeth. The solution to that case is to clogged up the damaged teeth. The purpose from this research is to describe theuse of clogged up materials in dental clinic over all health centers clinic in Bitung city in 2014.This research use descriptive retrospective design. The research sample is the entire patient medical record of patients with clogged up materials in all health centers of Bitung city that uses total sampling method during 2014. Total sampel that obtained are 27 sampel and categorized based on age, sex, and teeth region. The most used clogged up material during 2014 is GIC filling, age category that ranged from 26-55 years old are received most of clogged up treatment and female patients are the most who receive this treatment. Anterior teeth region is the most region teeth that receive composite clogged up and GIC in posterior regionKeywords: clogged up material, composit, GICAbstrak:Kesehatan merupakan hal yang penting bagi setiap manusia dan karies merupakan salah satu masalah kesehatan yang merusak struktur email dan dentin dari gigi dan penanggulangannya adalah dengan menumpat gigi yang mengalami kerusakan. Tujuan dari penelitian yaitu untuk mengetahui gambaran penggunaan bahan tumpatan di poliklinik gigi seluruh puskesmas yang ada di Kota Bitung pada tahun 2014. Penelitian menggunakan disain deskriptif dengan pendekatan retrospektif. Sampel penelitian ialah seluruh rekam medik pasien pengguna bahan tumpatan di seluruh puskesmas kota Bitung yang menggunakan metode total sampling selama 2014. Total sampel yang didapatkan 27 sampel dan dikategorikan berdasarkan umur, jenis kelamin dan regio gigi. Tumpatan yang paling banyak dipakai tahun 2014 adalah tumpatan GIC, kategori umur 26-55 tahun yang paling banyak menerima penumpatan, pasien perempuan paling banyak menerima perwatan tumpatan, regio gigi anterior paling banyak menerima tumpatan komposit dan posterior GIC.Kata kunci: bahan tumpatan, komposit, GIC.